Rehabilitation, Physical and Rehabilitation Medicine and Community Based Rehabilitation - a comment to the debate towards a differentiated view of PRM on rehabilitation system, services and training of rehabilitation professionals - Christoph Gutenbrunner; Boya Nugraha, MS, PhD (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
This comment aims to give a contribution to the debate about the best way to implement rehabilitationservices and, in particular, how specialist in Physical and Rehabilitation Medicine (PRM) define its rolein rehabilitation services in general and in Community Based Rehabilitation (CBR). The paper discussesthe use of the team rehabilitation and the definitions of CBR. A differentiated model of rehabilitationservices according to the phase of the disease and the intensity of service provision is developed. Theterm rehabilitation nowadays is used in two different ways: Rehabilitation as a health strategy or a set ofmeasures. The term CBR also is used in a dual way on the one hand describing a policy or managementstrategy or on the other hand describing the provision of “basic” rehabilitation services which is offered atthe community level. It is important to differentiate between acute, post-acute rehabilitation and long-termrehabilitation services to understand the need of different types of rehabilitation services. Additionally a5-level model of the intensity of rehabilitation services covers rehabilitation that is delivered by families,peers, neighbours, and others to highly specialized rehabilitation services, e.g. for acute rehabilitation orrehabilitation for severely affected patients. In comprehensive rehabilitation service, including CBR, the roleof PRM specialists is described in three ways: PRM deliver rehabilitation services, PRM act as an advisorand coordinator or PRM act as a trainer.Keywords: Rehabilitation definition, community based rehabilitation, rehabilitation services, Physical and Rehabilitation Medicine